Hair cortisol levels are associated with overweight and obesity in the ELSA-Brasil cohort - Rodrigues, Karine Lino; Scaranni, Patrícia de Oliveira da Silva; Pereira, Evelyn Nunes Goulart da Silva; da Silva, Vivian Vieira Dias; Silvares, Raquel Rangel; de Araujo, Beatriz Peres; Castilho, Cristina; Schmidt, Maria Inês; Fonseca, Maria de Jesus Mendes da; Griep, Rosane Harter; Daliry, Anissa (Frontiers in Endocrinology, 2024)
Introduction: Hair cortisol level has recently been identified as a promising marker for detecting long-term cortisol levels and a marker of hypothalamic-pituitary-adrenal cortex (HPA) axis activity. However, research on the association between obesity and an altered cortisol metabolism remains controversial. Objective: This study aimed to investigate the relationship between hair cortisol levels and overweight and obesity in participants from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) Methods: This was a cross-sectional study involving 2,499 participants from the second follow-up (visit 3, 2017-2019) attending research centers in Rio de Janeiro and Rio Grande do Sul states. Hair samples were collected, and cortisol levels were analyzed using enzyme-linked immunosorbent assay (ELISA) kits. Cortisol levels were classified as low (< 40 pg/mg), medium (40-128 pg/mg), or high (> 128 pg/mg). The participants were classified as eutrophic, overweight, or obese according to their weight (kg) and height (m 2 ). Odds ratios (ORs) with 95% confidence intervals (95%CI) were estimated. Results: Of the 2499 individuals, 30% had eutrophic weight, 40% were overweight, and 30% were obese. Notably, cortisol levels gradually increased with increasing body weight. Among participants with high hair cortisol levels, 41.2% were classified as overweight and 34.2% as obese. Multinomial logistic regression analysis indicated that participants with high cortisol levels were 43% (OR =1.43; 95%CI: 1.02-2.03) more likely to be overweight and 72% (OR =1.72; 95%CI:1.20-2.47) more likely to be obese than participants with low hair cortisol levels. After adjustment for all covariates, high cortisol levels remained associated with obesity (OR = 1.54; 95%CI:1.02-2.31) and overweight (OR =1.33;. Conclusion: In the ELSA-Brazil cohort, hair cortisol levels were positively associated with overweight and obesity. These results underscore the importance of considering stress and cortisol as potential factors in obesity prevention and intervention efforts, and highlight a novel aspect of the complex relationship between stress and obesity in the Brazilian population.